A sociological look at the concepts of youth and cultural practices: perspectives and reflections - Doutor, Catarina (Última Década, 2019)
Based on the clearly undeniable, polysemic nature of the concepts of youth and cultural practices, this article focuses on a reflection on the various theoretical perspectives. The main concerns of this article, which put an emphasis on the importance of young people and therefore their cultural practices in contemporary societies, are reflected on the following research questions: What does youth stand for? What is the meaning of being young in the world today? What are cultural practices understood? The article shows, therefore, how cultural practices are, fundamental to the daily lives of people, especially young people.